The Untold Stories behind Tearful Eyes in M.G. Vasanji’s ‘‘And Home Was Kariakoo: A Memoir of an Indian African’’ - Maridi, VEERABABU; Dakkumalla, Jyothirmai (International Journal of Language and Literary Studies, 2024)
Writing history about one’s own country is much easier than documenting the same diaspora in a foreign land. As it happened somewhere, most of their stories might go unnoticed, neglected or censored. It is the greatness of any writer to depict the antiquities with all possible facts without hurting the sentiments of the natives of those nations. One such genuine attempt was made by Indian-origin Tanzanian writer M.G.Vasanji. His memoir “And Home Was Kariako” is the best example for displaying us the predicament of the Indian diaspora on the Tanzanian soil. In this research we testify those alienations, migrations, dispossessions and ordeals of Indian migrants in East Africa are actualities which were little noticed by the rest of the world. To manifest those certitudes, the authors of the research referred number of other articles, books and visited some of the places which were mentioned by M.G. Vasanji in his book. We then wrapped up by canvassing Vasanji’s “And Home Was Kariakoo: A memoir by An Indian African” is a testimony to know the adversities of Asian aliens in East Africa.